Prostate Cancer (Exon Publications, 2022)
Prostate cancer is a life-altering diagnosis, not just for patients, but for their loved ones as well. Once, prostate cancer was most frequently diagnosed in men in their 60s and 70s; with increasing use of imaging modalities and PSA testing, the incidence is on the rise, and we are now seeing men in their 40s with the disease. This poses a challenge for clinical management depending on the stage of the disease—from watchful waiting or active surveillance to aggressive treatment with the risk of therapeutic nihilism. Despite being one of the most common cancers in Western men, its natural history, prognosis, and treatment are poorly understood. This book brings together a select faculty of experts to present a comprehensive view of the current state and future perspectives of prostate cancer. There are ten chapters in the book—the first four cover our present knowledge and understanding of the disease, the following three explore new advancements and treatments, particularly looking at overcoming resistance to therapy, and the remaining three chapters focus on specific molecules with the potential to become drug targets. We all have much to learn about prostate cancer. This book is aimed primarily at clinicians and scientists, but many areas will also be of interest to the layperson.